INFLUENCE OF SOIL HYDRODYNAMIC AND PHYSICOCHEMICAL PROPERTIES ON TEA GROWTH IN HILLY REGIONS: A CASE STUDY OF QINBA MOUNTAIN - Peng He; Ziru Niu; Tianqing Chen; Yang Zhang; Jichang Han; Zengguang Xu; Yutong Zhao (Journal of Animal and Plant Sciences, 2025)
This study used the Van Genuchten model to estimate soil hydrological processes in four different tea growth zones in the main tea-growing region of Qinba Mountain and analyzed the physicochemical properties of soils to provide a scientific basis for selecting and planning tea cultivation in hilly regions of China. The retention capacity of soil water, water release properties, unsaturated hydraulic conductivity, diffusivity of soil water and porosity in the various regions were also assessed. The analysis results showed that the tea plantations in the Qinba Mountains consisted primarily of muddy clay, while when growth was poor, both the water content and the bulk density were significantly higher compared to other growing areas and the sand content, organic matter and porosity were the lowest. Conversely, luxuriant growth had the highest sand content and the lowest silt content. The characteristic curve for soil moisture was precisely adjusted using the V-G model with an R2 value of over 0.99. In addition, the index K (x) =a*exp (b*x) effectively described water absorption and unsaturated hydraulic conductivity, resulting in an R2 value of over 0.90. The moisture content of the soil and the diffusivity of the soil water were cleverly modelled using the exponential function D (θ) =aebθ, with the R2 value exceeding 0.99. In the entire suction sector, the water holding capacity was rated as weak growth > moderate growth > well growth = lush growth. Optimal water delivery capacity was observed in areas of weak growth, while areas with well growth had the least favorable performance. The order of unsaturated hydraulic conductivity in the four areas was as follows: lush growth, well growth, moderate growth, and poor growth. In addition, the diffusivity of soil water gradually increased as the moisture content of the soil volume increased and approached an infinite increase as the volume moisture content approached saturation. When choosing hilly areas for growing tea, the optimal soil texture should be loose and well-aerated clay soil with higher sand and lower silt content, high porosity, low bulk density and high organic matter content. In addition, the high water diffusing capacity and the moderate water holding capacity of the soils enable effective drainage and water storage under various conditions.
Keywords: Tea growth; Hydrodynamic properties; Soil structure; Soil water characteristic curve